(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
The dynamic trade-off view of capital structure is based on partial adjustment models that find that firms adjust towards target levels. In this paper, we estimate the speed of adjustment based on the first difference of the lead leverage levels (actual lead) and lag leverage levels (actual lag) to the first difference of simulated lead (target) leverage levels and lag levels (actual lag leverage) for UK firms. Consistent with the literature we find that firms adjust the lag (current) leverage levels faster to lead levels when they are above lead levels relative to periods when they are below lead levels. This is due to managerial actions in minimizing present value of bankruptcy costs when firms are over-levered. Bringing in the market timing view of capital structure, we measure deviation of market prices to predicted theoretical values, and find that speed of adjustment is influenced by equity mispricing. We find that firms adjust faster to lead levels when lag levels are above lead levels and the extent of deviation above theoretical values is not excessive relative to when deviations of prices from theoretical levels are too high. Furthermore, looking at firms below lead levels, we find that firms adjust faster to lead levels when equities prices below theoretical values severely deviate; suggesting that firms increase debt issues when equity prices are acutely suppressed. This indicates managers are consistently looking at windows of opportunities when issuing or repurchasing to ensure successful timing attempts. Thus, our findings suggest that although market timing could also work within a trade-off framework where managers are timing based on the deviation from theoretical prices as well as moving towards simulated lead levels, the extent of the integration of both explanations of capital structure remains puzzling.